Assessing the Impact of Economic Growth on Regional Income Inequality: Evidence from the Papua Highlands, Indonesia (2022–2023) - Wenda, Dekis; Mollet, J.; Hutajulu, Halomoan (Journal of Regional Economics and Development, 2025)
Economic growth is often perceived as a driving force of development; however, it can simultaneously lead to widening income inequality, particularly in resource-dependent regions. This study investigates the effect of economic growth on income inequality in the Papua Highlands, Indonesia, during the period 2022–2023. Using secondary data from the Central Bureau of Statistics (BPS), the analysis employs a simple linear regression model to examine the relationship between Gross Domestic Product (GDP) growth and the Gini coefficient. The findings reveal a positive and statistically significant relationship between economic growth and income inequality, with a regression coefficient of 0.019 and an adjusted R² of 0.817. This indicates that regional economic expansion has contributed to the widening of income disparities across districts in the Papua Highlands. The results confirm the Kuznets hypothesis, which posits that inequality tends to increase in the early stages of economic growth before eventually declining. The study concludes that growth in the Papua Highlands has been concentrated in capital-intensive sectors such as mining and government administration, while local community participation remains limited. It recommends policies focused on equitable resource distribution, sectoral diversification, and inclusive development strategies.